NEW BOUNDS FOR TRUNCATION-TYPE ERRORS ON REGULAR SAMPLING EXPANSIONS - Atreas, Nikolaos D. (Numerical functional analysis and optimization, 2002)
We give some new estimates for the Truncation Error of sampling series of functions on regular sampling subspaces of . These estimates lower the well known Jagerman's bound on Shannon's sampling expansions.